2012
DOI: 10.1155/2012/841813
|View full text |Cite
|
Sign up to set email alerts
|

Study Structure and Properties of Nanocomposite Material Based on Unsaturated Polyester with Clay Modified by Poly(ethylene oxide)

Abstract: In recent years, polymer clay nanocomposites have been attracting considerable interests in polymers science because of their advantages. There are many scientists who researched about this kind of material and demonstrated that when polymer matrix was added to little weight of clay, properties were enhanced considerably. Because clay is a hydrophilic substance so it is difficult to use as filler in polymer matrix having hydrophobic nature, so clay needs to be modified to become compatible with polymer. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The extent of improvement obtained in this study is consistent with the UP/nanofillers reported in the literature. Thanh et al . reported an enhancement in tensile strength (12%) and elastic modulus (56%) in the presence of nanoclay at concentrations above 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of improvement obtained in this study is consistent with the UP/nanofillers reported in the literature. Thanh et al . reported an enhancement in tensile strength (12%) and elastic modulus (56%) in the presence of nanoclay at concentrations above 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…The role of nanoparticles with various shapes and properties like CNTs, GO, clay, carbon black, nanoalumina, nano calcium carbonate and nano titanium on the performance of UP resins has been investigated. In all cases the optimum improvement in mechanical properties can be achieved by a fine dispersion of nanoparticles providing the maximum interfacial area.…”
Section: Introductionmentioning
confidence: 99%
“…Montmorillinonite, as one of the most often studied materials for nanoreinforcement has been used as such, or modified by grafting of silanes, by ion-exchange [73], by polymers (e.g. polyethylene oxide) [74], or by quaternary alkylammonium modifiers [75]. Typically, organoclay-modified UPRs show increased impact strength, tensile strength, and modulus [76À78], better thermal stability [72], higher plasticity [75], and even lower shrinkage.…”
Section: Nanoclays As Fillers For Upr and Vermentioning
confidence: 99%
“…Anion concentration is listed as an important parameter to measure the air quality, and appropriate anion concentration is beneficial to human health and environmental improvement [3][4][5][6]. ARMA (anion rubber modified asphalt) possesses the double advantage of excellent performance and green environmental protection.…”
Section: Introductionmentioning
confidence: 99%